IMPLEMENTASI AUGMENTED REALITY SEBAGAI MEDIA PENGENALAN ALAT-ALAT LITURGI AGAMA KATOLIK BERBASIS ANDROID MENGGUNAKAN METODE MARKER BASED TRACKING - NAIBAHO, RIKY; Rosiska, Evan (LPPM Universitas Putera Batam, 2021)
Technology is always developing in various aspects, one of which is augmented reality technology. The existing media introduction has also been very developed, especially the media introduction made with augmented reality. Information delivery will also look more interesting and interactive when using augmented reality technology. Augmented reality is defined as a technology that combines 2D or 3D objects, then displayed in 3D and looks real.As in this study, an application was created using augmented reality technology about catholic liturgical equipment. The goal is to make the information obtained about catholic liturgical equipment more interesting and interactive as it increases people's interest in getting to know the catholic liturgical equipment. To create applications with augmented reality technology, one of them can use the marker based tracking method, namely by utilizing markers to be scanned and displaying objects in 3D. Therefore, the application using augmented reality technology for the introduction of catholic liturgical equipment can provide more interesting and interactive information.